Immunology and pathogenesis of canine demodicosis. Issue 5 (9th June 2014) - Ferrer, Lluis; Ravera, Ivan; Silbermayr, Katja
<x xml:space="preserve">Abstract</x> Demodex mites colonized the hair follicles and sebaceous glands of mammals millions of years ago and have remained relatively unchanged in this protected ecologic niche since then. The host immune system detects and tolerates their presence. Toll‐like receptor‐2 of keratinocytes has been demonstrated to recognize mite chitin and to elicit an innate immune response. The subsequent acquired immune response is poorly understood at present, but there is experimental and clinical evidence that this is the main mechanism in the control of mite proliferation. A transgenic mouse model (STAT−/−/CD28−/−) has demonstrated that the immune response is complex, probably involving both cellular and humoral mechanisms and requiring the role of co‐stimulatory molecules (CD28). It is known that a genetic predisposition for developing canine juvenile generalized demodicosis exists; however, the primary defect leading to the disease remains unknown. Once the mite proliferation is advanced, dogs show a phenotype that is similar to the T‐cell exhaustion characterized by low interleukin‐2 production and high interleukin‐10 and transforming growth factor‐β production by lymphocytes, as described in other viral and parasitic diseases. Acaricidal treatment (macrocyclic lactones) decreases the antigenic load and reverses T‐cell exhaustion, leading to a clinical cure. Although in recent years there have been significant advances in the management and understanding of this important and complex canine disease, more research in areas such as the aetiology of the genetic predisposition and the immune control of the mite populations is clearly needed.